The Impact of Debt Policy, Profitability, and Company Size on Firm Value - Tamba, Rani Rosya; Tsamara Nayla Safitri; Panjaitan, Gloria Oktavania; Nada Syifa Athaya; An Suci Azzahra (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the impact of debt policy, profitability, and company size on firm value in companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research adopts a quantitative approach, utilizing multiple regression analysis to evaluate the partial and simultaneous effects of the independent variables on firm value. The findings indicate that company size significantly influences firm value, as larger companies often exhibit operational stability and attract greater investor interest. The regression results show that company size (measured by the natural logarithm of total assets) has a t-value of -0.516 with a significance level of 0.610, indicating no direct effect on firm value. Profitability, measured by the gross profit margin, also shows no significant effect on firm value, with a t-value of -1.289 and a p-value of 0.206. Similarly, debt policy, represented by the Debt-to-Equity Ratio (DER), yields a t-value of 1.389 with a p-value of 0.174, suggesting that while debt policy has a positive direction, it does not significantly enhance firm value. The F-test result further confirms that the independent variables do not simultaneously affect firm value, with an F-statistic significance of 0.319 (greater than 0.05). These findings underscore the importance of optimizing company size, as larger firms inherently reflect better operational resilience and investment appeal. Additionally, the results highlight the need for careful management of financial risks associated with debt usage to maintain balance between growth and stability. This study contributes to the field of financial management by providing empirical evidence on the determinants of firm value in the Indonesian context.